Help Annonymous Project Report - Joshua Jasper Ashaba; Nahum Okello; Nabil Sengooba; Gensi Collin Ikiriza; Karongo Keron Kansiime; Elizabeth AmandaNamale (Uganda Christian University, 2024)
The "Help Anonymous" project, developed by a team from Uganda Christian University, represents a transformative approach to mental health support. Our application creates a safe space for anonymous dialogue, offering peer support, professional advice, and educational resources, thereby making mental health care accessible to a broader audience. This community-driven platform has shown significant user engagement and an increase in mental health awareness, demonstrating the effectiveness of our strategies. As a collective, we are proud to contribute to the United Nations' Sustainable Development Goals, specifically SDG 3 (Good Health and Well-being) and SDG 10 (Reduced Inequalities), by providing a platform that fosters open conversations on mental health and supports inclusivity. Our project underscores the importance of community and technology in breaking down barriers to mental health care and destigmatizing the pursuit of help. Moving forward, we are committed to enhancing our platform's reach and impact, driving positive change in the realm of mental health.